Variable-rate adaptive trellis coded QAM for flat-fading channels. - Lau, V.K.N (IEEE Transactions on communications)
A bandwidth-efficient variable-rate adaptive channel coding scheme, ATCQAM, for time-varying flat-fading channels is proposed. In addition to the forward channel, a low-capacity feedback channel is needed to convey channel state information to the transmitter, possibly with delays and noise. A number of transmission modes, with varying throughputs, are incorporated at the transmitter. Appropriate transmission modes are selected based on the feedback channel states. Design issues for the ATCQAM are considered. A closed-loop control scheme to maintain mode synchronization between the transmitter and the receiver is discussed. The effects of feedback delay, a noisy feedback channel, and mobile speed are investigated. Analytical bounds are derived and simulations are performed to verify the results